2015
DOI: 10.1186/s12887-015-0479-4
|View full text |Cite
|
Sign up to set email alerts
|

Newborn hearing screening programme in Belgium: a consensus recommendation on risk factors

Abstract: BackgroundUnderstanding the risk factors for hearing loss is essential for designing the Belgian newborn hearing screening programme. Accordingly, they needed to be updated in accordance with current scientific knowledge. This study aimed to update the recommendations for the clinical management and follow-up of newborns with neonatal risk factors of hearing loss for the newborn screening programme in Belgium.MethodsA literature review was performed, and the Grading of Recommendations, Assessment, Development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 124 publications
(125 reference statements)
1
33
0
6
Order By: Relevance
“…Results revealed the following evidence levels for associations between a given risk factor and delayed-onset hearing loss: (a) Strong levels included congenital CMV or ECMO therapy; (b) weak levels included genetic mutations, respiratory distress syndrome, or family history of hearing loss; and (c) no link included low birth weight or congenital toxoplasmosis. The discrepancies between these two comprehensive literature reviews are apparent: Although Vos et al (2015) found a high level of evidence linking toxoplasmosis and hearing loss, Beswick et al (2012) did not, and although Vos et al (2015) found a moderate level of evidence linking ECMO and hearing loss, Beswick et al (2012) found a stronger link. At the same time, there were also consistent findings: Both reviews found a high level of evidence linking congenital CMV and hearing loss, a moderate level linking family history and hearing loss, and little to no evidence linking low birth weight and hearing loss.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Results revealed the following evidence levels for associations between a given risk factor and delayed-onset hearing loss: (a) Strong levels included congenital CMV or ECMO therapy; (b) weak levels included genetic mutations, respiratory distress syndrome, or family history of hearing loss; and (c) no link included low birth weight or congenital toxoplasmosis. The discrepancies between these two comprehensive literature reviews are apparent: Although Vos et al (2015) found a high level of evidence linking toxoplasmosis and hearing loss, Beswick et al (2012) did not, and although Vos et al (2015) found a moderate level of evidence linking ECMO and hearing loss, Beswick et al (2012) found a stronger link. At the same time, there were also consistent findings: Both reviews found a high level of evidence linking congenital CMV and hearing loss, a moderate level linking family history and hearing loss, and little to no evidence linking low birth weight and hearing loss.…”
mentioning
confidence: 98%
“…Furthermore, only two recent literature reviews exist, and findings are mixed. For example, one meta-analysis completed by Vos, Senterre, Lagasse, Group, and Leveque (2015) evaluated risk factor studies from the years 2000 to 2015 by using the grading of recommendations, assessment, development, and evaluation (GRADE) assessment method to determine the level of evidence and strength of recommendation for each risk factor (Guyatt et al, 2008). Results revealed the following evidence levels for associations between a given risk factor and delayed-onset hearing loss: (a) Strong levels included congenital cytomegalovirus (CMV), toxoplasmosis, syphilis, or rubella; (b) moderate levels included a family history of hearing loss, hyperbilirubinemia, meningitis, or extracorporeal membrane oxygenation (ECMO) therapy; (c) weak levels included low Apgar scores; and (d) very low levels included congenital herpes, low birth weight, neonatal intensive care unit (NICU) stay, assisted ventilation, or ototoxic drugs.…”
mentioning
confidence: 99%
“…Taramanın doğumdan en az 12-24 saat sonra, emzirildikten 30 dk ile 1 saat içinde ve doğal uykuda iken yapılması, sedasyon için ilaç kullanılmaması önerilmektedir. 37,38 İlk taramadan "kalan"lar hastanede kalış süresine göre, taburcu olmadan önce bir kez daha taranmaktadır. Her taramada her iki kulak da taranmalıdır.…”
Section: Taramanin Kisitliliklariunclassified
“…Kemoterapi (sisplatin). 13,38 Belirtilen risk faktörlerinin varlığı, işitme kaybı riskini bu kişilerde en az 10 kat artırmakta-dır. 39 Pozitif aile öyküsü, intrauterin enfeksiyon, sendromik stigma, kraniyofasiyal anomali, nörode-jeneratif hastalık veya menenjit geçirenler ilk taramada işitme testinden geçseler dahi geç başlangıçlı işitme kaybı gelişme riski nedeni ile üç yaşına kadar altı ayda bir odyolojik değerlendirmelerinin yapıl-ması önerilmektedir.…”
Section: Taramanin Kisitliliklariunclassified
“…Hereditary causes can be classified as syndromic (Alport, Norrie, Usher, Pendred, Waardenburg, Jervell, and Lange-Nielsen) or non-syndromic (autosomal dominant, autosomal recessive, x-linked, or mitochondrial), and may be present at birth, show signs of progression, or manifest later in life, when the child is older. [2][3][4][5][6][7] Treatment options vary according to the underlying cause. Certain types of conductive hearing loss (e.g., otitis media with effusion, cholesteatoma etc.)…”
Section: Introductionmentioning
confidence: 99%